2008
DOI: 10.2478/v10019-008-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of electric field effects on cell membranes. A review for a critical selection of pulse duration for therapeutical applications

Abstract: Background. Electropulsation is one of the non-viral methods successfully used to transfer drugs and genes into living cells in vitro as in vivo. This approach shows promise in field of gene and cellular therapies. This presentation first describes the temporal factors controlling electropermeabilization to small molecules (< 4kDa) and then the processes supporting DNA transfer in vitro. The description of in vitro events brings our attention on the processes occurring before (s), during (ms) and after electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Several studies have investigated the influence of pulse parameters on the efficiency of electroporation [1], [12], [15], [33]- [35], [37], [46]. In general, these studies demonstrated that the same efficiency can be obtained with different combinations of pulse parameters.…”
Section: +mentioning
confidence: 99%
“…Several studies have investigated the influence of pulse parameters on the efficiency of electroporation [1], [12], [15], [33]- [35], [37], [46]. In general, these studies demonstrated that the same efficiency can be obtained with different combinations of pulse parameters.…”
Section: +mentioning
confidence: 99%
“…11,13 Electroporation is a nonviral physical method for facilitated delivery of various molecules into cells, including genes. [14][15][16] Electrically assisted gene delivery, called electrotransfection, increased transfection efficiency of either reporter genes or therapeutic genes compared with injection of gene alone. 17,18 To date several preclinical and clinical studies using electroporation (EP) and therapeutic genes for cancer treatment led to encouraging results demonstrating antitumor effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the electric field can later act within the cells and its effects are no longer limited to the cell membranes. The process of pore formation is very fast, but the pores remain open for much longer, depending on temperature [34][35][36][37]. Thus, once the pores are formed, the ionic current begins to flow through the cytoplasm and the dc electric field begins to act within the cell interior on the nucleus and cytoplasmic structures.…”
Section: Discussionmentioning
confidence: 99%